Sympathy for Oswald Mosley: Politics of Reading and Historical Resemblance in the Moral Imagination of an English Literary Society. (3rd January 2022) - Reed, Adam
Abstract: The mid-twentieth-century English novelist, Henry Williamson, wrote nature stories but also romantic and historical fiction, including a fifteen-volume saga that contains a largely favorable characterization of Oswald Mosley, the leader of the British Union of Fascists. This essay considers the challenge of such a fascist character through the prism of the literary imagination of Williamson readers, and more specifically through my longstanding ethnographic work with an English literary society constituted in the author's name. I am centrally concerned with how literary society members deal with the positive depiction of the Mosley-based character through the stages of the reading process that they identify and describe. Do the immersive values commonly attached to their solitary reading culture, for instance, assist or further problematize that engagement? What role does their subsequent, shared practice of character evaluation play? As well as considering the treatment of characters as objects of sympathy, I explore the vital sympathies that for literary society members tie characters together with historical persons. Across the essay I dialogue with anthropological literature on exemplars, historical commentaries on the fascist cult of leadership, and finally with the philosophical claims that Nussbaum makes for the moral and political consequences of fiction reading.